Status and problems of off-campus student teaching in three teachers colleges for elementary teachers - Uthaipan, Sin 1933- (s.n.], 1971)
This study investigated the status and problems of off-campus student teaching programs in three teacher colleges for elementary teachers namely: the National Teacher's College, Philippine Normal College, and the University of the Philippines. College supervisors reported that the most serious problems of student teachers have something to do with "class control and management" and "the use of teaching aids".